Conditions for awarding the degree of habilitated doctor and the title of professor in accordance with law and practice of the council of scientific excellence - Janczewski, Zbigniew (Prawo Kanoniczne, 2024)
On July 20, 2018, another act was published, the second in the 21st century, regulating issues of higher education in Poland. It is called the Law on Higher Education and Science. The statutory regulations include issues related to the awarding of doctoral and habilitated doctor degrees and the title of professor. This publication deals with two - habilitation and professorship. Specifically, it analyses the statutory conditions for awarding the above-mentioned academic degrees and titles.